(untitled) - Serway, Raymond A. (Belmont, CA., 2004)
Serway (professor emeritus, James Madison University) and Jewett (physics, California State Polytechnic University) integrate Web-based media resources in this sixth edition of an introductory physics text for students majoring in science or engineering. Other new features in this sixth edition include quizes, pitfall preventions, and the addition of a general problem-solving strategy. Chapters on modern physics have been updated, and there are new problems.
Keywords: Physics